SIMULATION AND EXPERIMENTAL ANALYSIS OF CRYSTALLITE SIZE AND MACROSTRAIN OF HEMATITE (Fe2O3) NANOPARTICLES USING WILLIAMSON-HALL METHOD - Chiromawa, Idris Muhammad; Shitu, Ibrahim Garba; Muhammad, Aminu; Katibi, Kamil Kayode; Durumin Iya, Sani Garba (FUDMA JOURNAL OF SCIENCES, 2024)
Determining the crystallite size of nanoparticles represents a significant challenge due to the limitations associated with using a single estimation method. This study addresses this challenge by examining the structural properties of synthesized hematite (Fe2O3) nanoparticles through a combination of experimental and simulated X-ray diffraction analyzes (XRD). Using VESTA software, a simulated XRD pattern was created based on precise crystal structure details from a CIF file, accurately confirming the high purity and crystallinity of the synthesized hematite nanoparticles. Various Williamson-Hall models, including the Uniform Deformation Model (UDM), the Uniform Stress Deformation Model (USDM), and the Uniform Stress Energy Density Model (USEDM), were used to estimate crystallite size and microstrain. Comparing the results of both experimental and simulated data revealed slight variations attributed to differences in measurement techniques, sample preparation, and material properties. Furthermore, energy dispersive X-ray (EDX) analysis confirmed the elemental composition of the synthesized nanoparticles, while transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM) provided further validation of the particle size. This study provides a comprehensive investigation of the structural properties of hematite nanoparticles (Fe2O3) and highlights the importance of integrating multiple analytical techniques and simulation methods to improve the precision and reliability of crystallite size estimation.